2019
DOI: 10.5664/jcsm.7912
|View full text |Cite
|
Sign up to set email alerts
|

Association of Positive Airway Pressure Use With Acute Care Utilization and Costs

Abstract: Study Objectives: The current value-based medical climate has led to scrutiny of all medical costs. Given the relationship between obstructive sleep apnea (OSA) and many significant comorbid medical conditions, treating patients with OSA via positive airway pressure (PAP) therapy might reduce health care expenditures. Our goal was to determine the relationship between PAP use and acute care utilization and costs. Methods: This was a retrospective cohort study of adult patients who initiated PAP therapy after a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 27 publications
(26 reference statements)
0
10
0
Order By: Relevance
“…A recent study by Kirsch et al . reported that use of PAP at least 4 hours/night over an 18-month period in participants with moderate-severe OSA was associated with lower inpatient visits and costs compared with non-adherers [44]. Our study adds to the body of evidence that long-term adherence to PAP therapy can beneficially impact healthcare costs.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…A recent study by Kirsch et al . reported that use of PAP at least 4 hours/night over an 18-month period in participants with moderate-severe OSA was associated with lower inpatient visits and costs compared with non-adherers [44]. Our study adds to the body of evidence that long-term adherence to PAP therapy can beneficially impact healthcare costs.…”
Section: Discussionmentioning
confidence: 74%
“…The increase in health-related costs is reflected in a broad spectrum of services affecting inpatient, outpatient, emergency, and pharmacy-related costs [34, 43-45]. Conceptually, positive airway pressure (PAP) therapy should mitigate the impact of OSA on healthcare utilization; however, the overall body of evidence is limited and its results are mixed [34, 44-47]. Furthermore, recent technological advances in PAP devices have resulted in the ability to remotely monitor objective measures of PAP adherence over time.…”
mentioning
confidence: 99%
“…Since that time, two additional studies have found a beneficial effect on PAP. Kirsch and colleagues 27 analyzed data from a large health system in the Southeastern US. These investigators found a linear dose-response relationship between objective CPAP adherence data and acute healthcare costs, including reductions in inpatient stays and acute care visits.…”
Section: Economic Impact Of Obstructive Sleep Apnea Treatmentsmentioning
confidence: 99%
“…17 These include improved daytime alertness, 23 improved blood pressure control [24][25][26] (particularly in those with resistant hypertension 24 ), possibly reduced insulin resistance and improved glycemic control in diabetic patients, 27,28 improved quality of life, 23,29 reduced rates of drowsiness-related crashes, 12,[30][31][32] and lower risk of both cognitive deficits and cardiovascular disease. 23,33,34 In the workplace, lower health care costs [35][36][37] and rates of disability, 38 reduced absenteeism and occupational incidents, and improved productivity have been associated with PAP use. 39 PAP therapy also has been shown to improve all-cause mortality.…”
Section: Introductionmentioning
confidence: 99%